2021
DOI: 10.1002/casp.2583
|View full text |Cite
|
Sign up to set email alerts
|

‘You don't take things too seriously or un‐seriously’: Beyond recovery to liminal and liminoid possibility in a community arts and mental health project

Abstract: Recent years have seen a renewed interest in integrating creative activities into statutory mental health practice in high-income countries. In this article, we offer an exploratory analysis of an arts project delivered within UK mental health services, Creativity for Enablement and Wellbeing (CREW). Drawing on data collected for a process evaluation of the project, we suggest that conceptualising CREW as liminal and liminoid provides a helpful way to articulate the processes, atmospheres, relationships, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The process of homemaking, according to Kuttner, begins with symbolic embodiment in physical space and is then sustained through caring, respectful, and loving relationships. Laver et al (2021) also note the resonances between project Creativity for Enablement and Wellbeing, and Watkins and Shulman's (2008) public homeplaces as spaces that connect individual and social experience in mutually transforming ways. Other papers also describe community arts spaces that bring together people from diverse backgrounds, supporting the sharing of ideas and perspectives and the formation of community across difference (Beauregard et al, 2020;Epstein et al, 2021;Laver et al, 2021;Soulsby et al, 2021;Sonn et al, 2015).…”
Section: Amarachimentioning
confidence: 99%
See 3 more Smart Citations
“…The process of homemaking, according to Kuttner, begins with symbolic embodiment in physical space and is then sustained through caring, respectful, and loving relationships. Laver et al (2021) also note the resonances between project Creativity for Enablement and Wellbeing, and Watkins and Shulman's (2008) public homeplaces as spaces that connect individual and social experience in mutually transforming ways. Other papers also describe community arts spaces that bring together people from diverse backgrounds, supporting the sharing of ideas and perspectives and the formation of community across difference (Beauregard et al, 2020;Epstein et al, 2021;Laver et al, 2021;Soulsby et al, 2021;Sonn et al, 2015).…”
Section: Amarachimentioning
confidence: 99%
“…Laver et al (2021) also note the resonances between project Creativity for Enablement and Wellbeing, and Watkins and Shulman's (2008) public homeplaces as spaces that connect individual and social experience in mutually transforming ways. Other papers also describe community arts spaces that bring together people from diverse backgrounds, supporting the sharing of ideas and perspectives and the formation of community across difference (Beauregard et al, 2020;Epstein et al, 2021;Laver et al, 2021;Soulsby et al, 2021;Sonn et al, 2015). Across some of these examples, there were broader commonalities which bound them together, such as geographic location, allowing for greater heterogeneity.…”
Section: Amarachimentioning
confidence: 99%
See 2 more Smart Citations
“…In [7], it found that art-based mindfulness has improved the students' moods and improve their general well-being. In [10], it discussed that there is increasing interest in integrating creative activities into statutory mental health practice, especially in high-income countries. In the same study, the art project is found to engage individuals and improve general mental well-being.…”
Section: Introductionmentioning
confidence: 99%